Pengaruh Satisfaction, Trust dan Confidence Benefit Terhadap Customer Commitment Pada Produk Taplus BNI (Studi Kasus pada PT. Bank Negara Indonesia (Persero) Tbk Kantor Cabang Utama Musi Palembang ) - zakaria Wahab; Odor Pita Uli Bakara (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2011)
There has been considerable concern about how ongoing consolidation in financial systems around the world will affect competition. Indeed, much of the recent public debate seems to assume that perfect competition in banking is ideal. Such a thing will force each bank to understand how to make their customers satisfied. This research was aimed to examine how trust and confidence benefit on customer commitment affect the customer’s satisfaction. To understand this isntance, questionnaires were distributed to the target respondents. Samples were taken using convenience sampling. Total respondents of 100 were obtained. Using both descriptive and statistical analysis, results were obtained. Regression analysis was implemented. Based on partial analysis, results showed that trust and confidence benefit have significant influence to the customer commitment, while satisfaction do not provide  a significant influence to the customer commitment . Finally on the basis of the finding, recomendations that is to improve and to maintain  the performance of  independent variables (trust and confidence benefits) and especially on the confidence benefit variable  have been made. Keywords : Satisfaction, Trust, Confidence Benefit , Customer Commitment